The State density index as a category for the analysis of infant mortality in Peru. An exploratory analysis - Murillo, Juan Pablo (2017)
Infant mortality is one of the most sensitive indicators for assessing the living conditions and well-being of populations. It is also a valuable indicator for analyzing the deployment of interventions in the territory linked to public health. The study proposes to explore the extent to which the State density index is useful to understand the deployment of infant mortality in the territory and to contextualize its associated factors. For the data and the study period analyzed and in reference to the values of the 2007 Census, we highlight there is a limited relation of the State density index as a variable associated with infant mortality. Its usefulness as a criterion for the analysis of groups is emphasized, allowing a finer discrimination of the inequities and of the differential characteristics associated with the infant mortality at the provincial level.